The effect of perceived value on farmers’ livestock manure resource utilization behavior: Evidence from Shandong, China - Gao, Runze; Liu, Guoliang; Fan, Yuze; Wang, Xueyang; Ren, Zhong (Frontiers in Psychology, 2023)
The rapid development of animal husbandry has brought many problems such as ecological environmental pollution and public health damage. The resource utilization of livestock manure is the key way to deal with the above crisis and turn waste into treasure. Based on the theory of perceived value, this paper uses multi-group structural equation model to explore the driving mechanism of perceived value on the resource utilization behavior of livestock manure. The results showed that: (1) The resource utilization behavior of livestock manure followed the logic of "cognitive level → cognitive trade-off → perceived value → behavioral intention → behavioral performance". Perceived benefit and perceived risk have positive and reverse driving effects on perceived value respectively. Perceived value has a positive driving effect on behavioral intention. Behavioral intention has a positive driving effect on utilization behavior. (2) Among the observed variables of perceived benefits, ecological benefits have the greatest impact; Among the observed variables of perceived risk, economic risk has the greatest impact. Among the observed variables of perceived value, Significance cognition has the greatest influence. Among the observed variables of behavioral intention, utilization intention has the greatest influence. (3) The perceived value has a differential effect on the utilization behavior of livestock manure resources of different part-time farmers, and the driving effect is more obvious for full-time farmers. Therefore, it is necessary to improve the resource utilization system of livestock manure, increase the channel for realizing the output of manure resources, strengthen technical assistance and policy subsidies, and implement policies according to local conditions to improve the overall perceived value of farmers.